The Many Faces of Strategic Voting Tactical Behavior in Electoral Systems Around the World - Aldrich, John; Stevenson, Laura B.; Blais, André (University of Michigan Press, 2018)
Strategic voting is classically defined as â€œvoting for one's second preferred option to prevent one's least preferred option from winning when one's first preference has no chance.â€_x009d_ Voters want their votes to be effective, and casting a ballot that will have no influence on an election is undesirableâ€"therefore, some voters cast a strategic ballot when they decide it is useful. This edited volume includes case studies of strategic voting behavior in Israel, Germany, Japan, Belgium, Spain, Switzerland, Canada, and the UK, and provides a conceptual framework for understanding strategic voting behavior in all types of electoral systems.